EKSISTENSI ISLAM DI ASIA TENGGARA - Andi Herawati (Ash-Shahabah : Jurnal Pendidikan dan Studi Islam, 2018)
IslamIslam entered Southeast Asia in the VII as the initial stage of the formation of a muslim community consisting of traders. Later in the XIII century until the XVI century, has seen an Islamic-style kingdom which is the result of the spread of Islam. A country that is predominantly muslim because Islam is accepted and spread by the royal authorities then socialized and developed in the lower or lower community with the top dawn pattern. It is seen in the development and religious life in Brunei Darussalam and Malaysia relatively good and safe. Compared to other Southeast Asia countries, such as Indonesia, Singapore and Myanmar. The entry of Islam in Southeast Asia not only affects politics, but also in social, cultural, and economic terms.